Legal Review Of The Rights Of Child Prisoners At The Lubuk Pakam Correctional Institution - Bisbon Sibutar-Butar; Yasmirah Mandasari Saragih (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Children in conflict with the law (ABH) who enter the detention center still have the right to be protected by law. So that legal protection for ABH is very important to run. that the existence of a child protection must be sought if we want to seek national development that can be satisfactory. Therefore, to strengthen the legal protection of children even if they are already in detention, there are several regulations that apply in the ius constitutum in Indonesia. The regulation according to the doctrine is called Child Law, which is a set of legal regulations governing children. This research is descriptive analysis. Data collection is carried out using documentation studies where all secondary data used in this study are collected using library research. Data processing is carried out to facilitate the analysis of data that has been obtained in accordance with the problems studied. Data analysis used in this research is qualitative analysis. Qualitative analysis is a specification of the nature of research to examine between theory and practice on the protection and rights of child prisoners at Lubuk Pakam Correctional Institution. Special coaching institutions are regulated in Law Number 3 of 1997 concerning juvenile courts article 61 paragraph (2), Law Number 11 of 2012 concerning the Juvenile Criminal Justice System article 82 paragraph (1), and Law Number 23 of 2002 Article 9 paragraph (1) concerning child protection where in the education system provided to juvenile prisoners in accordance with their interests and talents, juvenile prisoners are entitled to obtain their rights such as education just like children who are not in conflict with the law or loss of independence in accordance with their interests and talents, and if there are juvenile prisoners who have abilities from others will get special education.